2016
DOI: 10.1021/acs.joc.5b02821
|View full text |Cite
|
Sign up to set email alerts
|

An Energetic Guide for Estimating Trifluoromethyl Cation Donor Abilities of Electrophilic Trifluoromethylating Reagents: Computations of X–CF3 Bond Heterolytic Dissociation Enthalpies

Abstract: This work established an energetic guide for estimating the trifluoromethyl cation-donating abilities (TC(+)DA) of electrophilic trifluoromethylating reagents through computing X-CF3 bond (X = O, S, Se, Te, and I) heterolytic dissociation enthalpies. TC(+)DA values for a wide range of popular reagents were derived on the basis of density functional calculations (M06-2X). A good correspondence has been identified between the computed TC(+)DA values and the experimentally observed relative trifluoromethylating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 129 publications
0
27
0
Order By: Relevance
“…All of these sulfonium-based reagents possess a similar aromatic core structure. In the process of studying derivatives of 409 , it was found that the reactivity can be further enhanced by the introduction of electron-withdrawing groups; 260 moreover, sulfonate groups have been used to increase the reagents’ solubility in water and thus simplify purification. 267 As shown in Scheme 68b, nucleophiles can be directly engaged in fluoroalkylation reactions in polar solvents and under mild conditions.…”
Section: Sulfonium Saltsmentioning
confidence: 99%
“…All of these sulfonium-based reagents possess a similar aromatic core structure. In the process of studying derivatives of 409 , it was found that the reactivity can be further enhanced by the introduction of electron-withdrawing groups; 260 moreover, sulfonate groups have been used to increase the reagents’ solubility in water and thus simplify purification. 267 As shown in Scheme 68b, nucleophiles can be directly engaged in fluoroalkylation reactions in polar solvents and under mild conditions.…”
Section: Sulfonium Saltsmentioning
confidence: 99%
“…We began by investigating a range of commercially available trifluoromethylating agents and found that trifluoromethyldibenzothiophenium salt A (Umemoto's reagent) was optimum 11, 12. Thus, reaction of A with the boronate complex generated from furan‐2‐yllithium and cyclohexylboronic ester 1 a gave the desired product 2 a (ca.…”
mentioning
confidence: 99%
“…[15] Such substituent effects remarkably differ from our previously reported linear Hammett dependence of the trifluoromethyl cation-donating ability on substituent constants for Togni's reagents 1f. [16] It can be easily rationalized by the insensitivity of neutral free radicals to electronic effects. When two MeO are located at the 4 and 5 positions (1d8), the BDE increases by 3 kcal/mol.…”
Section: Resultsmentioning
confidence: 99%